Pengaruh Budaya Organisasi, Komunikasi, Dan Work-Life Balance Terhadap Kinerja Karyawan (Studi Pada Pt. Bpr Gisawa, Bali) - Luh Meira Khirana Dewi; Dewiwati Sujadi (Universitas Triatma Mulya, 2025)
This study aims to determine and analyze the influence of organizational culture, communication, and worklife balance on employee performance at PT BPR Gisawa, Bali. The research method used is a quantitative method with a sample of 44 employees. The data analysis techniques used are descriptive analysis, data instrument testing, classical assumption testing, multiple linear regression analysis, t-test analysis, and beta coefficient analysis. The results of the analysis show a regression model of Y = 13.856 + 0.186 X1 + 0.175 X2 + 0.193 X3. From the results of this study it can be concluded that 1) organizational culture has a positive and significant effect on employee performance at PT BPR Gisawa, Bali 2) organizational culture has a positive and significant effect on employee performance at PT BPR Gisawa, Bali 3) worklife balance has a positive and significant effect on employee performance at PT BPR Gisawa, Bali 4) Work-life balance variables have a dominant influence on employee performance at PT BPR Gisawa, Bali, this can be seen in the Standardized Coefficients Beta of 0.390, organizational culture variables of 0.338 and communication variables of 0.325. The implementation that can be given from this study is for the management of PT BPR Gisawa to pay more attention to corporate culture, openness and adjustment of employee working hours.